The Semantical Analysis of the Film "Grand Budapest Hotel" - Nazmah Khairun Nisa, Bella Safira; Adinda Rianditta Vitara; Devi K Wulandari; Rizky Hafis Ramadhan; Khairun Nisa, Nazmah (Global Expert: Jurnal Bahasa dan Sastra, 2024)
This research analyzes semantics, metaphor, idiom, ambiguities, anomaly sentence in the film “The Grand Budapest Hotel”. The purpose of this study is to identify the types of sentences used by the characters in the film as well as to understand the meaning of the dialog between the speaker and the listener selected for this study. The findings of this study show that there are several semantic sentences, ambiguities, idioms, and anomalies. The results of this study are expected to provide a deeper understanding of meaning and representation in the movie The Grand Budapest Hotel, highlighting the importance of context and intention in interpreting meaning in communication. Keywords: Semantic, Methapor, Idiom, Ambiguities, Anomaly